The effectiveness of the guided inquiries learning model on the critical thinking ability of students - Mariya Solikah; Dian Novita (Jurnal Pijar Mipa, 2022)
This study aims to analyze the effectiveness of the guided inquiry learning model on the student's critical thinking skills on the sub-material factors that affect the rate of reaction. The research uses a quantitative method of pre-experimental type with the one-group pretest-posttest design. The instrument used implementation observation sheets, student learning activities, skills pretest-posttest questions, cognitive pretest-posttest questions, and response questionnaires. The research showed some findings. Firstly, the guided inquiry learning model implementation at the first meeting got a percentage of 97.4%, the second meeting it was 93.4%, with a very good category. Secondly, student activities during the learning process that get a larger percentage are more relevant than those that are not relevant—thirdly, improving critical thinking skills based on the significance of 0.000 below 0.05 so that it is accepted. Fourth, the cognitive domain learning outcomes of 11th grade MIPA 4 students at SMAN 19 SURABAYA score 75, which is declared complete with an average n-gain value of 0.85 and classical completeness of 100%. Finally, student responses to the applied learning model were very good, with a percentage of 99.6%.